2021
DOI: 10.1097/md.0000000000028371
|View full text |Cite
|
Sign up to set email alerts
|

Buyang huanwu decoction combined with probiotics or prebiotics for functional recovery from stroke

Abstract: Background: Stroke is a global disease that compromises human health. Considering the side effects of Western medicine, alternative medicine, such as Chinese medicine, is widely used. Concurrently, the research and development on the microbiota-gut-brain axis in recent years have made intestinal microflora the new target of treatment. We aim to scientifically evaluate the advantages and clinical guidance of using Buyang-Huanwu (BYHW) decoction combined with probiotics in the intestinal microflora.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The risks of bias in the trials are shown in Table 3 and Figure 2, and Figure 3. All 39 trials included in this study explicitly used random sequence generation, of which 18 described the randomization methods in detail (random number table method for 16 trials: Liang et al, 2021;Yang 2022;Zuo and Lin, 2020;Zhang, 2018;Xu et al,2017;Xiang, 2019;Wu, 2021;Sui, 2014;Shi, 2016;Li and Wei, 2021;Li, 2019;Jiang, 2019;Ji, 2016;Han, 2014;Fang et al, 2019;Chen and Cao, 2016; random alphabet method for one trial: (Meng et al, 2014); random envelope method for one trial: (Du, 2018). The other 21 articles described the use of randomization but did not provide detailed information on the methods of randomization.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks of bias in the trials are shown in Table 3 and Figure 2, and Figure 3. All 39 trials included in this study explicitly used random sequence generation, of which 18 described the randomization methods in detail (random number table method for 16 trials: Liang et al, 2021;Yang 2022;Zuo and Lin, 2020;Zhang, 2018;Xu et al,2017;Xiang, 2019;Wu, 2021;Sui, 2014;Shi, 2016;Li and Wei, 2021;Li, 2019;Jiang, 2019;Ji, 2016;Han, 2014;Fang et al, 2019;Chen and Cao, 2016; random alphabet method for one trial: (Meng et al, 2014); random envelope method for one trial: (Du, 2018). The other 21 articles described the use of randomization but did not provide detailed information on the methods of randomization.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…"This prescription treats hemiplegia, crooked eyes, slurred speech, salivation at the corners of the mouth, dry stools, frequent urination, and incontinence of enuresis" (Wu, 2019). This prescription has the compatibility characteristics of "not to remove blood stasis to activate blood, but to invigorate Qi to activate blood" (Liang et al, 2021). Astragalus trimestris L is the monarch drug in BYHWT, which has the effects of nourishing vitality, promoting blood circulation, and removing blood stasis; Angelica sinensis (Oliv.)…”
Section: Figurementioning
confidence: 99%